The Effect of City Development on Temperature in The City of Semarang - sutriani; Emilya Nurjani; Sri Rum Giyarsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
Semarang City is one of the most densely populated cities in Central Java Province, which has experienced land conversion due to increased development. The purpose of this study is to analyze the relationship and influence of urban development on temperature in the urban area of Semarang from 1980 to 2020. Population data, land use changes, temperature change data from 1980 to 2020, and remote sensing images were used.The influence of city development and temperature used inferential statistics, which is a method related to data analysis for forecasting or drawing conclusions about the overall data. Regression analysis is one part of inferential statistics that is widely used in the decision-making process. Semarang is experiencing development, both in terms of physical appearance and population growth. The population continues to increase until it almost doubles over a period of 40 years, which is directly proportional to the increase in temperature in the city of Semarang. The results of the analysis show that the development of the city seen from changes in population and changes in built-up land has an effect on temperature changes in the city of Semarang by up to 69.9%. The spatial distribution of temperature changes shows the direction of the center of Semarang City activities in the Districts of Central Semarang, North Semarang, East Semarang, South Semarang, and Gajah Mungkur, which is also in accordance with the condition of the area, which is also a residential area and the city center.